Dynamic water patterns change the stability of the collapsed filter conformation of the KcsA K+ channel - Wu, Di (PloS one, 2017)
The selectivity filter of the KcsA K+ channel has two typical conformations-the conductive and the collapsed conformations, respectively. The transition from the conductive to the collapsed filter conformation can represent the process of inactivation that depends on many environmental factors. Water molecules permeating behind the filter can influence the collapsed filter stability. Here we perform the molecular dynamics simulations to study the stability of the collapsed filter of the KcsA K+ channel under the different water patterns. We find that the water patterns are dynamic behind the collapsed filter and the filter stability increases with the increasing number of water molecules. In addition, the stability increases significantly when water molecules distribute uniformly behind the four monomeric filter chains, and the stability is compromised if water molecules only cluster behind one or two adjacent filter chains. The altered filter stabilities thus suggest that the collapsed filter can inactivate gradually under the dynamic water patterns. We also demonstrate how the different water patterns affect the filter recovery from the collapsed conformation.